“Welcome to the Revolution”: Promoting Generational Renewal in Argentina’s Ni Una Menos - Friedman, Elisabeth Jay (2023)
Despite the global upsurge of youth-fueled mass mobilization, the critical question of why new generations may be eager to join established movements is under-explored theoretically and empirically. This study contributes to theories of feminist generational renewal in particular. We examine the longer-term movement context and more proximate strategies that have enabled young women to participate steadily in a cycle of protest, alongside more seasoned activists, due to a process of feminist learning and affective bonding that we call “productive mediation.” We focus on the Argentine Ni Una Menos (Not One Less) massive yearly march, which, since its onset in 2015, demonstrates that feminist activists have achieved the sought-after goal of fostering a highly diverse mass movement. These large-scale mobilizations against feminicide and gender-based violence gain much of their energy from a strong youth contingent, so much so that they have been called “the Daughters’ Revolution.” We show that these “daughters” have been welcomed by previous generations of feminist changemakers. Drawing on original qualitative research featuring 63 in-depth interviews with activists of different ages, backgrounds, and locations across Argentina, we find that long-standing movement spaces and brokers, as well as innovative frameworks of understanding, repertoires of action, and organizational approaches, help to explain why preexisting social movements may be attractive for young participants.